Assessment of Static Resilience of Objects in the Rail Transport - Zdeněk Dvořák; Nikola Chovančíková; Katarína Hoterová; Michal Szatmári (Communications - Scientific letters of the University of Zilina, 2021)
Resilience is the ability of an object to retain its basic functions in the case of adverse events from an external or internal environment. Adverse events can jeopardize the operation of an object or cause it to become completely inoperable. The assessment of static resilience should be dealt with mainly by objects that are included in local, regional, national, and international critical infrastructure. ritical infrastructure is the basis of today’s modern functioning society. The paper is focused on design of the static resilience evaluation of objects in the rail transport. The proposed method of static resilience assessment is based on safety pillars and is applied in a case study to a specific object of the rail transport. This approach is original in the conditions of the Slovak Republic.